Anthropometric and performance measures to study talent detection in youth volleyball - Melchiorri, G.; Viero, V.; Triossi, T.; Annino, G.; Padua, E.; Tancredi, V. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of this work was to study anthropometric and performance measurements in 60 young male volleyball players (YV) and 60 youth not active in the sport (YNA) to assess which of these would be more useful to study the characteristics of potential performers.